PERAN IMAM MAULANA ABDUL MANAF AMIN AL-KHATIB DALAM GERAKAN PEMBAHARUAN KAUM TRADISIONAL DI BATANGKABUANG KOTA PADANG - Rahmi Yusra; Za’im Rais; Zulfis Zulfis (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2026)
This research is motivated by the limited scholarly attention to the role of local scholars in Islamic reform movements in Minangkabau, particularly the contribution of Imam Maulana Abdul Manaf Amin al-Khatib from Batang Kabung, Padang City. Amid the tension between local Islamic traditions—such as surau, Sufi orders, and manuscript culture—and the rise of modern Islamic reform, Imam Maulana emerged as a key figure capable of bridging both worlds. This study aims to describe his biography and socio-religious background, analyze his contributions to Islamic reform, and explain the impact of his religious thought and practices on the Batang Kabung community. A descriptive qualitative method was employed, using document analysis of manuscripts, literature review, and examination of local historical sources. The findings indicate that Imam Maulana played a significant role in educational reform through the development of Madrasah Tarbiyah Islamiyah (MTI), in preserving Islamic intellectual heritage through manuscript production, and in promoting a moderate and socially responsive model of religious leadership. His ideas and practices strengthened the community’s religious identity, harmonized local customs with Islamic teachings, and enabled society to face modernity without losing its traditional roots. This study affirms that Imam Maulana represents an essential model of a local scholar functioning as an agent of Islamic reform in Minangkabau.